Test automation and numerical calculation of calibration parameters for wake probes - Yana V. Ivanova (Труды Крыловского государственного научного центра, 2018)
Object and purpose of research. This paper studies five- and six-point spatial probes, as well as their rakes used in hydrodynamic tests of models with propellers in KSRC Deepwater Towing Tank. The purpose of this work was to upgrade Kanal 3 software & hardware system supporting calibration tests of wake rakes. Materials and methods. Probes are calibrated by means of software and hardware tools, as well as by means of KU-68 coordinate device. Calibration coefficients are calculated through biparametric approximation. Here, correction to the non-aligned position of the coordinate device has to be calculated and taken into account. Main results. New software has been developed for automated acquisition and processing of data on probe and rake calibration. The novel feature of calculations is that now they take into account the non-alignment correction for KU-68 coordinate device. Test results are used in measurements of velocity and pressure fields in the propeller plane behind the model. The new software made these tests handier and their data processing several times faster. Conclusion. Kanal-3 hardware and software complex supporting experimental determination of calibration coefficients for wake rakes made up by five- and six-point probes has been successfully upgraded.